PERENCANAAN DRAINASE KOTA SEBA - Krisnayanti, Denik S.; Hunggurami, Elia; Dhima-Wea, Kristina N. (Jurnal Teknik Sipil, 2017)
Drainage aims to drain the water from an area that comes from rain water and waste water, in order to avoid excessive inundation. The purpose of this study is planned drainage system in the city of Seba to drain water during the rainy season to prevent inundation of rainfall that is too big. The drainage zone divided into 4 zone based one the contour and the water canal that would be canalized. The divided zone also based on Seba Region RDTR (2011). Based on the calculation of the results obtained by the rectangular canal as many as 44 canals and a trapezoid shape as many as 21 canals. Canal base width (b) the average for the rectangular-shaped canal is 0.80 m, while the trapezoidal canal average of 0.50 m. The width of the surface of the trapezoidal canal average of 0.65 m. Planning drainage canals adapted to existing research data canals at the sites. There are 12 canal base width of the canal remains were taken from the existing canal data, while existing canals steeper modified according to plan based on the calculation of flood discharge plan